Investigating sodium reduction in the UK diet through salt particle design and understanding contributions of food oral processing on perception - Hurst, Katherine (2022)
The global food industry urgently requires effective sodium reduction solutions to increase health credentials and align with changing salt reduction targets. Previously investigated strategies for sodium reduction in potato crisps (e.g. salt enhancers, replacers and direct salt removal) have proven limitations and challenges. Therefore, studies presented in this thesis focused on redesigning salt particles to deliver optimum saltiness in snacks by developing and validating a range of physicochemical design rules to achieve effective salt reduction. It is also important to consider variations in consumer perception due to inter-individual differences in oral processing parameters and their impact on dietary intake. Therefore, the relationship between salivary parameters, saltiness perception and dietary intake, and the impact of mouth behaviour type on the perception and liking of potato crisps were also investigated. Physicochemical design rules for salt particles were established by measuring adhesion properties, dissolution and temporal saltiness perception of a diverse range of salts (n = 8) with varying physical and chemical properties (size, density, shape, hydrophobicity and flow properties). Findings determined that salt particles should be small in particle size, have a low density, low hydrophobicity and an optimised particle shape. Optimised model salts identified in this study were used to validate the design rules when topically applied to potato crisps. Inter-individual differences in salivary flow rate and sodium concentration affected salt taste threshold but did not predict the perceived saltiness intensity of supra-threshold concentrations. Furthermore, the high salt taste sensitivity group consumed significantly more salt than the low salt taste sensitivity group, suggesting that ‘salt-responsive’ individuals seek more salt-containing foods, or high salt consumers may develop these behaviours due to their diet. The selected optimised model salts and established particle design rules enabled a 30 % salt reduction in potato crisps while maintaining saltiness perception and consumer acceptance. Comparatively, only 15 % salt reduction was achieved without sensorial impact by directly removing salt. Other potential strategies investigated did not enhance saltiness perception or product liking, highlighting the utility of design rules to develop new optimised salt particles. Mouth behaviour type did not impact saltiness liking or perception of potato crisps. However, the ‘suckers’ group liked the texture of the whole product set significantly less than the other mouth behaviour classifications (crunchers, chewers, smooshers). This research contributes to the knowledge of salt reduction strategies in snack foods, specifically around the developed physicochemical design rules and the importance of considering individual salivary parameters when assessing the perception of saltiness. The physicochemical design rules developed within this research could also be utilised in other flavour particles to facilitate sugar reduction and optimise flavour delivery.